Genotyping-by-sequencing of a melon (Cucumis melo L.) germplasm collection from a secondary center of diversity highlights patterns of genetic variation and genomic features of different gene pools. (December 2017) - Pavan, Stefano; Marcotrigiano, Angelo; Ciani, Elena; Mazzeo, Rosa; Zonno, Vito; Ruggieri, Valentino; Lotti, Concetta; Ricciardi, Luigi
Abstract Background Melon (Cucumis melo L.) is one of the most important horticultural species, which includes several taxonomic groups. With the advent of next-generation sequencing, single nucleotide polymorphism (SNP) markers are widely used in the study of genetic diversity and genomics. Results We report the first successful application of genotyping-by-sequencing (GBS) technology in melon. We detected 25, 422 SNPs by the analysis of 72 accessions collected in Apulia, a secondary centre of diversity in Southern Italy. Analyses of genetic structure, principal components, and hierarchical clustering support the identification of three distinct subpopulations. One of them includes accessions known with the folk name of 'carosello ', referable to thechate taxonomic group. This is one of the oldest domesticated forms ofC. melo, once widespread in Europe and now exposed to the risk of genetic erosion. The second subpopulation contains landraces of 'barattiere ', a regional vegetable production that was never characterized at the DNA level and we show was erroneously considered another form ofchate melon. The third subpopulation includes genotypes of winter melon (C. melo var.inodorus ). Genetic analysis within each subpopulation revealed patterns of diversity associated with fruit phenotype and geographical origin. We used SNP data to describe, for each subpopulation, the average linkage disequilibrium (LD) decay, and to highlight genomic regions possibly resulting from directional selection and associated with phenotypic variation. Conclusions We used GBS to characterize patterns of genetic diversity and genomic features withinC. melo . We provide useful information to preserve endangered gene pools and to guide the use of germplasm in breeding. Finally, our findings lay a foundation for molecular breeding approaches and the identification of genes underlying phenotypic traits.